The complete mitochondrial genome of the Fancy Pigeon, Columba livia (Columbiformes: Columbidae). (28th January 2015) - Zhang, Rui-Hua; Xu, Ming-Ju; Wang, Cun-Lian; Xu, Tong; Wei, Dong; Liu, Bao-Jian; Wang, Guo-Hua
Abstract: The fancy pigeons are domesticated varieties of the rock pigeon developed over many years of selective breeding. In the present work, we report the complete mitochondrial genome sequence of fancy pigeon for the first time. The total length of the mitogenome was 17, 233 bp with the base composition of 30.1% for A, 24.0% for T, 31.9% for C, and 14.0% for G and an A–T (54.2 %)-rich feature was detected. It harbored 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes and 1 non-coding control region (D-loop region). The arrangement of all genes was identical to the typical mitochondrial genomes of pigeon. The complete mitochondrial genome sequence of fancy pigeon would serve as an important data set of the germplasm resources for further study.